An Exploration: The Impact of Covid19 Towards the Learning Activities at Institut Parahikma Indonesia (IPI) Gowa - Patur Rahman (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2021)
The purpose of this study is to find out the Students & Lecturers’ experiences about the impacts of Covid19 toward the learning quality, method, and students’ emotion. This research employed qualitative descriptive case study design which was applying phenomenological approaches that focused on personal knowledge, paradigm and subjectivity. The subjects of the study were the seventh and the fifth semester of the whole academic majors at Institut Parahikma Indonesia in the odd semester of the academic year 2021/2022. The respondent of this study was 4 students and 2 lecturers. Data obtained using a qualitative questionnaire which consisted by open-ended questions. The data analysis technique used gathering past experiences, data transcription, sample extraction, theme identification, and combining phenomenon until saturation of data was achieved. The result described 4 major outlines by the impact of Covid-19 towards learning activities such as quality loss in learning activities, Technical Issue and learning limitation, and students’ emotion.